2018
DOI: 10.1111/odi.12883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the three Enterococcus faecalis strains on apoptosis in MC3T3 cells

Abstract: Together, the clinically isolated strains of E. faecalis can induce apoptosis in MC3T3 osteoblasts, which may be attributed to the regulation of interaction between members of the Bcl-2 family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
(39 reference statements)
2
15
0
Order By: Relevance
“…Endodontic research community has been mostly concerned with microbiology, histopathology, diagnosis and treatment of AP (de Miranda & Colombo, ; Kruse, Spin‐Neto, Reibel, Wenzel, & Kirkevang, ; Kudo et al, ; Li, Tong, & Ling, ; Ricucci, Loghin, Gonçalves, Rôças, & Siqueira, ). Yet, understanding the aetiology of disease requires other information than that related to biological mechanism in the individual.…”
Section: Introductionmentioning
confidence: 99%
“…Endodontic research community has been mostly concerned with microbiology, histopathology, diagnosis and treatment of AP (de Miranda & Colombo, ; Kruse, Spin‐Neto, Reibel, Wenzel, & Kirkevang, ; Kudo et al, ; Li, Tong, & Ling, ; Ricucci, Loghin, Gonçalves, Rôças, & Siqueira, ). Yet, understanding the aetiology of disease requires other information than that related to biological mechanism in the individual.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is crucial to examine the role of E. faecalis on osteoblast apoptosis in PAP. Our previous study found that E. faecalis strains from the root canals of teeth with PAP trigger apoptosis in mouse MC3TE-E1 and human MG63 cell lines [10,12]. However, the effect of E. faecalis on apoptosis in human primary osteoblasts and its mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of E. faecalis in infected root canals has been associated with the occurrence of periapical lesions larger than 3 mm, indicating the role of E. faecalis in PAP and endodontic treatment failure [9]. Recent studies have found that E. faecalis induces apoptosis in mouse osteoblast-like MC3T3 cells and human osteosarcoma MG63 cells [10][11][12]. However, there may be a difference between the effect of E. faecalis infection in primary osteoblasts and osteoblast-like cells from different origins [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013, Li et al . 2018). Consistent with the above studies, this study also found that live E. faecalis displayed a remarkable reduction of MG63 cell viability in a MOI dose‐ and infection time‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%